TIPE KEPRIBADIAN TOKOH UTAMA DALAM NOVEL PADA SEBUAH KAPAL KARYA NH DINI (Sebuah Analisis Psikologi Sastra) - Dyna Nur Shuhupy; Hera Wahdah Humaira; Fauziah Suparman (LPSDI Bina Patria, 2023)
Literary psychology is the study of psychology. Psychology describes the human psyche in the real world. While human psychology literature in the world of fiction. In this study, the focus is on personality psychology or the personality type of the main female character in the novel Pada Sebuah Kapal by Nh. Dini uses a descriptive qualitative method with the aim of describing the personality type of the main female character. There are four personality types, namely sanguinis personality type, choleric personality type, melancholic personality type, and phlegmatic personality type. Each person has a unique mixture, namely a natural mixture, a mixture of complements and a mixture of opposites. Based on the results of research on the main female character in the novel Pada Sebuah Kapal, she has a perfect melancholy personality type with a natural blend of peaceful phlegmatic and a complementary mixture of popular sanguine, and a mixture of opposites between perfect melancholy and popular sanguine